Phytochemical and Antimicrobial Studies of Medicinal Plant Costus Speciosus (Koen.) - Aparna Saraf (E-Journal of Chemistry)
The present paper deals with the phytochemical and antimicrobial screening of therapeutic importance from Costus speciosus (Koen.), an important medicinal plant. The study involves the preliminary screening and qualitative HPTLC separation of secondary metabolites from the rhizome of Costus speciosus (Koen.). The in vitro antibacterial activity was performed against a few pathogens viz. E. coli, Staphylococcus aureus, Klebsiella pnuemoniae and Pseudomonas aeruginosa. The generated data has provided the basis for its wide use as the therapeutic both in traditional and folk medicine.